IMPLICATIONS OF TECHNOLOGY TRENDS IN EDUCATION: USING BIG DATA FOR LEARNING ANALYTICS - Rahmawati (International Journal of Teaching and Learning, 2024)
Big Data technology trends have a significant impact on education. With its ability to collect, store, and analyze large amounts of data, Big Data can provide valuable insights into the learning process and help improve its effectiveness. Big Data has a significant role and contribution in learning analytics. With its ability to collect, store, and analyze large amounts of data, Big Data can provide valuable insights into the learning process and help improve its effectiveness. The use of Big Data technology in education has significant implications in learning analytics. The use of Big Data technology in education has the potential to improve learning effectiveness, personalize learning, data-based decision making, develop relevant curricula, and monitor and evaluate the learning process. Big Data has an important role and contribution in learning analytics. With its ability to collect, store, and analyze large amounts of data, Big Data can provide valuable insights into the learning process and help improve its effectiveness.